A Na-containing Pt cocatalyst for efficient visible-light-induced hydrogen evolution on BaTaO2N. Issue 24 (5th May 2021) - Li, Huihui; Lu, Daling; Chen, Shanshan; Hisatomi, Takashi; Vequizo, Junie Jhon M.; Xiao, Jiadong; Wang, Zheng; Lin, Lihua; Xiao, Qi; Sun, Yuliang; Miseki, Yugo; Sayama, Kazuhiro; et al.
Abstract : A well-dispersed Pt cocatalyst obtained using Na as a promoter provides enhanced photocatalytic hydrogen evolution over BaTaO2 N under visible light. Abstract : A high degree of cocatalyst dispersion and intimate contact with the photocatalyst are vital for improving the activity of narrow bandgap photocatalytic materials. In this work, the addition of a small number of Na ions to a Pt cocatalyst deposited on a semiconducting BaTaO2 N photocatalyst (with an absorption edge of 650 nm) enhanced photocatalytic H2 evolution under visible light irradiation. The addition of Na ions to the Pt-loaded BaTaO2 N (Pt/BaTaO2 N) caused more efficient evolution of H2 than Na-free Pt/BaTaO2 N during Z-scheme overall water splitting. These results should assist in the fabrication of photocatalysts modified with highly dispersed cocatalysts for efficient water splitting.